Pengaruh Motivasi Kerja dan Displin Kerja terhadap Kinerja Karyawan pada PT. JNE Medan (Kampung Lalang) - Siti Hasanah; Harum Anisa; Bella Uci Sapitri Br S Meliala; Ariqa Shafa Nurelf; April Novi Kristiani Telaumbanua; Dwi Fanny Fransiska Dewi Butar-Butar (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study aims to determine the effect of work motivation and work discipline on employee performance at PT Tiki Jalur Nugraha Ekakurir (JNE) Kampung Lalang, a logistics and delivery service company. Optimal employee performance is the result of a combination of internal drive (motivation) and compliance with work regulations (discipline). This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to respondents who are operational employees at JNE Kampung Lalang. Data were analyzed using multiple linear regression assisted by SPSS software. The results showed that work motivation has a positive and significant effect on employee performance with a coefficient value of 1.000 and a significance of 0.000. Conversely, work discipline has a negative but significant effect on employee performance with a coefficient value of -0.388 and a significance of 0.000. This finding indicates that increasing work motivation can encourage increased employee performance, while negative results from work discipline. This study emphasizes the importance of management in properly understanding the internal factors that influence performance so that the policies implemented do not have a counterproductive impact.